Influence of chemical compounds on the forming of electric ARC - Vakulenko, I. O.; Plitchenko, S. O.; Makarevych, D. M. (Science and Transport Progress, 2014)
Purpose. The purpose of work is a comparative analysis of chemical compounds influence on the process of electric arc forming and condition of its burning. Methodology. Material for an electrode was a wire 3 mm in diameter of low carbon steel with contain of carbon 0.15%. As chemical compounds, which determine the terms of forming of arc welding were used kaolin; CaCO3 with the admixtures of gypsum to 60%; SiO2 and Fe – Si with the iron concentration to 50%. Researches were conducted at the use of direct electric current and the arc of reverse polarity. As a source of electric current the welding transformer of type PSO-500 was used. On the special stand an initial gap between the electrode and metal-plate was equal to 1–1.5 mm. The interelectrode interval was filled with the probed chemical compounds and it was formed an electric arc. In the moment of electric arc arise the values of electric current and the arc voltage were determined. After the natural break of electric arc, the final size of the gap between electrodes was accepted as the maximal value of the arc lengths. Findings. In the conditions of experiment the metal transfer in interelectrode interval corresponded to the drop mechanism. According to external characteristics the ratio between the maximal arc length and the power of electric discharge has the appearance of exponential dependence. Specific power of electric arc characterizes environment of interelectrode interval in the moment of arc forming per unit of its length. Originality. 1. On the basis of influence analysis of the studied chemical compounds on the formation processes of electric arc inversely proportional relationship between the power of the electric current and the maximum arc length to the moment of its natural break is defined. 2. The ratio between the maximal arc length and the power of electric current with sufficiently high correlation coefficient is subjected to the exponential dependence. Influence of the studied compounds on the process of electric arc forming is determined using the degree values of the obtained ratio. 3. The value of specific power of electric current in the moment of electric arc forming per unit of its length can be accepted as the parameter, which characterizes the environment in the interelectrode interval. Practical value. In the conditions of identical adjusting strength of electric current it is determined the gradation of the studied chemical compounds in the order of increase of their influence on the process of the arc burning. Kaolin has the minimum influence and Fe – Si – the maximal one.